2010
DOI: 10.1292/jvms.09-0284
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Chinese Herb Chai-Hu-Gui-Zhi-Tang Extract on Water Immersion Restraint Stress-Induced Acute Gastric Ulceration in Rats

Abstract: ABSTRACT. It is well known that maintenance therapy using Chai-hu-gui-zhi-tang (CHGZT), a traditional Chinese medicine, has been proven to prevent the recurrence of peptic ulcers. However, little is known as to whether or not it has protective effects against acute gastric injury. In the present study, we investigated the preventive effects of pretreatment with CHGZT extract on the development of water immersion restraint stress-induced acute gastric ulceration in male Wistar rats. The CHGZT extract (50, 250, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Among various animal models of stress, water-immersion restraint stress (WIRS) has been widely accepted for studying SIGMI. Previous studies demonstrated the immediate appearance of multiple gastric lesions in the gastric mucosa in rats subjected to WIRS for 3.5 hours [5][6][7][8], confirming the reproducibility of this model.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Among various animal models of stress, water-immersion restraint stress (WIRS) has been widely accepted for studying SIGMI. Previous studies demonstrated the immediate appearance of multiple gastric lesions in the gastric mucosa in rats subjected to WIRS for 3.5 hours [5][6][7][8], confirming the reproducibility of this model.…”
Section: Introductionsupporting
confidence: 64%
“…The WIRS method of inducing gastric lesions was first described by Takagi and Okabe (1968) [24]. Following that, the WIRS method was used widely by investigators to demonstrate the appearance of multiple gastric lesions in the gastric mucosa in rats, confirming its reproducibility [7,[25][26][27]. Hence, it remains relevant as a reliable model for use in studies related to SIGMI.…”
Section: Discussionmentioning
confidence: 99%
“…Physical and psychological stresses can play a major risk factor for the occurrence of gastric ulcerations [3638]. The WIRS model has been reported to mimic the clinical acute gastric ulcers due to trauma, surgery, or sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The WIRS model has been reported to mimic the clinical acute gastric ulcers due to trauma, surgery, or sepsis. It has been widely used in stress-induced gastric ulcer studies [36, 38, 39]. Water-immersion and restraint stress reduces the synthesis of PGE 2 in gastric mucosa and induces the production of reactive oxygen species [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Water immersion restraint stress (WIRS) is widely accepted for studying stress ulcers and can also mimic the clinical acute gastric ulcerations caused by trauma, surgery, or sepsis. 9 It has been reported that oxidative stress generated by infiltrated neutrophils and the xanthinexanthine oxidase system and its subsequent lipid peroxidation is involved in the development of gastric mucosal lesions induced by WIRS. 10 WIRS is also known to provoke acute inflammation in gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%